I (Don't) Like You! But Who Cares? Gender Differences in Same Sex and Mixed Sex Teams - Leonie Gerhards; Michael Kosfeld (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the effect of likability on female and male team behavior in a lab experiment. Extending a two-player public goods game and a minimum effort game by an additional pre-play stage that informs team members about their mutual likability we find that female teams lower their contribution to the public good in case of low likability, while male teams achieve high levels of cooperation irrespective of the level of mutual likability. In mixed sex teams, both females' and males' contributions depend on mutual likability. Similar results are found in the minimum effort game. Our results offer a new perspective on gender differences in labor market outcomes: mutual dislikability impedes team behavior, except in all-male teams.
Keywords: C90; J16; 330; gender differences; likability; experiment; team behavior